Ethical and legal aspects of the abortion - Ambros, Mauro Cabrera (2009)
The aim of this work was to perform an up-to-date study about the ethical and forensic aspects of abortion. To accomplish that, the Brazilian law about this subject as well the legislation of several other countries were investigated. The legal and ethical aspects concerning the abortion were equally analyzed. The search was performed in diverse reports of Forensic Medicine, Penal Law and Medical Ethics, which are referred to at the article references.